2003
DOI: 10.1093/nar/gkg152
|View full text |Cite
|
Sign up to set email alerts
|

Basal transcriptional regulation of human damage-specific DNA-binding protein genes DDB1 and DDB2 by Sp1, E2F, N-myc and NF1 elements

Abstract: The human DDB1 and DDB2 genes encode the 127 and 48 kDa subunits, respectively, of the damage-specific DNA-binding protein (DDB). Mutations in the DDB2 gene have been correlated with the hereditary disease xeroderma pigmentosum group E. We have investigated the proximal promoters of the DDB genes, both of which are G/C-rich and do not contain a TATA box. Transient expression analysis in HeLa cells using a luciferase reporter system indicated the presence of core promoters located within 292 bp (DDB1) and 220 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…The DDB2 mouse gene (Ensembl Gene ID ENSMUS-G00000002109) was analysed and a putative E2F binding site, also reported by others (Nichols et al, 2003), was identified located 143-136 nucleotides upstream of the translation initiation site.…”
Section: Chip For Ddb2mentioning
confidence: 68%
See 2 more Smart Citations
“…The DDB2 mouse gene (Ensembl Gene ID ENSMUS-G00000002109) was analysed and a putative E2F binding site, also reported by others (Nichols et al, 2003), was identified located 143-136 nucleotides upstream of the translation initiation site.…”
Section: Chip For Ddb2mentioning
confidence: 68%
“…This finding provides for the first time, a plausible mechanism for the cell cycle regulation of expression of DDB2 as upon Rb phosphorylation in G1/S, E2F activity also increases to peak in S phase (for reviews, see Dyson, 1998;Muller and Helin, 2000). Whether E2F transcriptionally regulates DDB2 in other species remains to be confirmed, but the identification of an E2F site downstream of the initiation of transcription site in human DDB2 suggests that this may also be the case in human cells (Nichols et al, 2003).…”
Section: Ddb2 Is Expressed In Mouse Tissues and Affects Dna Repairmentioning
confidence: 77%
See 1 more Smart Citation
“…One possibility is that E2F1 regulates the expression of one or more rate-limiting factors involved in NER. E2F1 overexpression can transcriptionally activate several genes whose products have been implicated in the repair of UV-induced DNA damage, including DDB2, BRCA1 and MSH2 (Wang et al, 1999;Hartman and Ford, 2002;Meira et al, 2002;Polager et al, 2002;Ren et al, 2002;Takimoto et al, 2002;Nichols et al, 2003;Young et al, 2003). To determine if inactivation of endogenous E2f1 would affect the expression of DNA repair genes, microarray gene expression analysis was performed using RNA isolated from the epidermis of wild-type and E2f1 À/À mice (data not shown).…”
Section: E2f1 Regulation Of Dna Repairmentioning
confidence: 99%
“…However, the removal from DNA of many bulky lesions, including photoproducts, occurs in the absence of DDB (8,12,13), and DDB2 is induced by UV-irradiation at a time by which NER has been completed. Moreover, the DDB2 promoter resembles that of a cell cycleregulated gene (1,14), and DDB2 is part of the COP9 signalosome complex (15,16). Instead, DDB2 has been proposed to be a transcription transactivator through its stimulation of E2F1 (17), and we recently observed that DDB2 controls p53-mediated apoptosis after UV-irradiation of human diploid fibroblasts and that XP group E (XP-E) primary skin fibroblasts are abnormally resistant to killing by UV-irradiation (18).…”
mentioning
confidence: 99%